2012
DOI: 10.4103/2277-9531.99969
|View full text |Cite
|
Sign up to set email alerts
|

Fruit and vegetable intake, body mass index and waist circumference among young female students in Isfahan

Abstract: Background:Obesity is growing rapidly in our country. Nutrition is an important issue of obesity. The aim of this study was to determine the association between fruit and vegetable intake with the waist circumference and the body mass index (BMI) among young female university students.Materials and Methods:This cross-sectional study was conducted on 236 healthy female university students aged between 18 and 30 years old, who were selected randomly from the students of Isfahan University of Medical Sciences, Ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Higher fruit and vegetable intakes are related to a yellower appearance of the skin [35,40]. Women with higher BMI were found to consume less fruits and vegetables [40,41], which, in turn, might result in lower skin yellowness.…”
Section: Discussionmentioning
confidence: 99%
“…Higher fruit and vegetable intakes are related to a yellower appearance of the skin [35,40]. Women with higher BMI were found to consume less fruits and vegetables [40,41], which, in turn, might result in lower skin yellowness.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that more than four servings of F/V intake per day were associated with a low risk of central obesity in adult women [ 34 ]. However, F/V intake may play different roles in the development of central obesity among women across different menopausal statuses [ 35 , 36 ]. For pre-menopausal women, a study from Korea indicated that a high F/V intake per day was associated with a low risk of central obesity [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…For pre-menopausal women, a study from Korea indicated that a high F/V intake per day was associated with a low risk of central obesity [ 35 ]. Still, another Isfahan research did not find significant correlations among women aged < 30 years [ 36 ]. For post-menopausal women, no significant correlation was observed between F/V intake and central obesity [ 35 ].…”
Section: Introductionmentioning
confidence: 99%